Pemanfaatan Tesaurus dalam Pembelajaran: Sebuah Tinjauan Sistematis - Azzahrawaani, Zhafirah; Agustina, Susanti (Universitas Sebelas Maret Library, 2023)
The learning process uses many foreign terms and synonyms, so various media are sometimes used in the learning process to provide understanding related to a term. One of them is a thesaurus commonly used to provide meanings and similarities in words so that students know the meaning and synonyms of the terms. A thesaurus is a list of words that have the same meaning and are arranged lexicographically. This study aims to determine thesaurus research trends in the realm of education or learning and the use of thesaurus as a learning medium and learning support. A systematic search of study literature was conducted based on the PRISMA framework. The population of this study is scientific articles indexed by Scopus with a span of the last five years that discuss related to thesaurus and education. Analysis of the literature revealed that thesaurus can be used as an additional learning medium to improve student understanding. Thesaurus development in each branch of science is needed because the thesaurus as a learning tool can support students understanding of the concentration of science they choose.